The Effect of the Application of the Problem Based Learning (PBL) Learning Model on Early Childhood High Order Thinking Skill (HOTS): A Quasi-Experimental Study - Alisia, Nurul; Martuty, Arie; Syamsuardi, Syamsuardi; Bahri, Aliem; Intisari, Intisari; Amri, Nur Alim; Hasbur, Heni Safitri (JURNAL PENDIDIKAN USIA DINI, 2025)
This study aims to investigate the effect of the application of the Problem Based Learning (PBL) learning model on higher order thinking skills (HOTS) in early childhood. This study used a pre-experimental design  with the One Group Pretest-Posttest model, involving 15 children aged 5–6 years in a private kindergarten in the Gatot Subroto area. The PBL model is applied through activities that allow children to observe phenomena, identify problems, design solutions, and draw conclusions independently. Data collection was carried out through observation of high-level thinking skills at two stages, namely before and after PBL treatment. The results of descriptive statistical analysis showed an increase in the average score from the pretest by 26.67 to 52.53 in the posttest. The Wilcoxon Signed-Rank test showed a significance value (2-tailed) = 0.001 < 0.05, which indicates a significant effect of the application of PBL on the improvement of children's high-level thinking skills. These findings suggest that PBL is effective in developing analytical, critical, and creative thinking skills in early childhood. The implication of the results of this study is the need to integrate problem-based learning models in the early childhood education curriculum as a strategy to optimize cognitive development and children's readiness to face future challenges